The peculiarities of macroscopic status of the upper gastrointestinal tract mucosa in patients with hepatic and extrahepatic portal hypertension. - Yu. M. Stepanov; N. V. Chaliy; O. V. Simonova (Medičnì Perspektivi)
Identification of endoscopic signs of concomitant pathology of the upper gastrointestinal tract allows to determine the tactics of managing patients with different forms of portal hypertension (PG). The analysis of macroscopic picture of esophagus, stomach and duodenum mucosa was carried out in 104 patients with portal hypertension (88 patients with hepatic  portal hypertension, 46 – with extrahepatic portal hypertension, 16 – without  portal hypertension). The frequency of changes in the esophagus, specific for  gastroesophageal reflux disease did  not differ significantly in the researched groups. The frequency and severity  of varicose veins of the esophagus were diagnosed more often in patients with hepatic form of portal hypertension (OR=10.0, p<0.05). The predominance of different pathological changes of the gastric mucosa in patients with extrahepatic form of portal hypertension was revealed. Portal gastropathy in this group was 5.3 times higher than in patients with hepatic hypertension and 21 times higher than in the III group (without portal hypertension) (p<0.01). There were no significant differences of endoscopic picture of the duodenum  mucosa between the researched groups.